(6√2/√3+√6)-(4√3/√6+√2)+(2√6/√2+√3)
Answers
Answered by
3
Step-by-step explanation:
Solution is in theAttachment.
First rationalize the denominator of each term by multiplying its conjugate in both the numerator and denominator and simplify it.
Conjugate of a first term (√2+√3) is
(√2-√3)
Conjugate of second term (√6+√3) is (√6-√3)
Conjugate of third term (√6+√2) is (√6-√2)
In denominator FORMULA used=
(a+b)(a-b)= a² - b²
=========================================================°======
Attachments:
![](https://hi-static.z-dn.net/files/d07/7e20e98b1ebc47f4e8706ba5b031f404.jpg)
![](https://hi-static.z-dn.net/files/d46/62b43b082065469e5d13b21378abe45c.jpg)
Similar questions
Math,
6 months ago
English,
6 months ago
India Languages,
6 months ago
Biology,
1 year ago
Economy,
1 year ago
Math,
1 year ago
Business Studies,
1 year ago